DIA-based quantitative proteomic analysis on porcine meat quality at different chilling rates - Yuqiang Bai; Tongjing Yan; Fei Fang; Xin Li; Su Wang; Juan Li; Chengli Hou; Dequan Zhang (Food Science and Human Wellness)
The objective of this study was to evaluate the effects of chilling rate on porcine meat quality from the perspective of proteome using data independent acquisition (DIA)-based quantitative proteomic strategy. M. longissimus thoracis et lumborum (n = 9) was assigned randomly to the control group (3.72 ℃/h), very fast chilling-Ⅰ group (VFC-Ⅰ, 9.31 ℃/h) and VFC-Ⅱ group (14.43 ℃/h). The DIA was used to analyze the difference in proteins under different chilling rates. Results showed that tenderness was improved significantly in meat at the chilling rate of 14.43 ℃/h. Seventy-nine differential abundant proteins (fold change >1.5, P <0.05), including 46 up-regulated and 33 down-regulated proteins, were identified and mainly involved in carbon metabolism, pyruvate metabolism and proteasome pathways. These pathways indicated that VFC delayed cell metabolism and glycolysis by down-regulating the expression of metabolic enzymes. The tenderness was improved by up-regulating the expression of proteasome and m-calpain.